Estrutura de famílias de crianças com câncer em cuidados paliativos: estudo à luz do modelo Calgary - Oliveira, Thaís Costa de (2018)
Introduction: palliative care in the field of pediatric oncology aim to improve the life quality of the child with câncer, through the promotion of a humanized and integral care during the illness process and in the phase of terminality, as well as it propitiates support for the family. This dissertation is constituted by two articles, the first, the revision one is entitled: Palliative care and the child with cancer: bibliometric study. Objective: to analyze the scientific production published in online journals on palliative care and the child with cancer. Methodology: this is a bibliometric study, performed with a sample of 58 articles, published between 2006 and 2016 and selected in databases LILACS, MEDLINE e BDENF. Results: the years of 2013 and 2016 presented a higher quantitative of publications. From the 38 selected journals for the study, the one that published more on the thematic was the magazine Pediatric Blood Cancer. The United States of America was the country that presented the higher number of published articles. The publications produced by researches of the Nursing area and authors with doctor’s degree prevailed. Conclusion: the study demonstrated that there is a reduced number of disseminated publications in national and international online journals on palliative care related to child with cancer. The second is entitled: Family structure of child with cancer in palliative care: study in the light of Calgary Model of Family Evaluation. Objective: to analyze the family structure of children in palliative care in the light of Calgary Model of Family Evaluation. Methodology: this is a field research of qualitative nature and participated in the study five families of children with cancer in palliative care, represented by their genitors. The research took place in a support house for children and adolescents with cancer, located in the city of João Pessoa – PB, Brazil. To allow data collection were utilized the interview technique and the instruments genogram and ecomap to delineate internal, external structures and family context. This one occurred in the period from April to June 2017. Empirical material was analyzed in the light of Cangary Model of Family Evaluation. Results: the results from three aspects of family estructure: internal structure, external structure and context, it was possible to identify that from compositions of the families of the study, three are nuclear extended and two single parent. In what regards support network, most referred to friend, family and church support. The families of the study reported having a good relationship with neighbors. All mothers of children with cancer highlighted the importance of religion and spirituality to face the process of their sons’ sickness. Conclusion: genogram and ecomap instruments indicated to be of great relevance to better comprehend the family structure of children with cancer under palliative care, as well as they are of supreme relevance to plan the assistance of nursing to the child with cancer and its family.